Parameterizing the basal melt of tabular icebergs. (October 2018) - FitzMaurice, Anna; Stern, Alon
Highlights: Upstream flow properties are not representative of iceberg basal flow properties. A Taylor column of reduced flow forms under large icebergs. Two conflicting representations of the heat transfer coefficient exist in ice melt parameterizations. A new parameterization of tabular iceberg basal melt is proposed, accounting for these factors. Abstract: In this study, we consider the influence of icebergs on the ocean when they are modeled as occupying physical space, to answer the question of how the melting of icebergs and subsequent distribution of meltwater in the water column might be accurately parameterized in climate models. Iceberg melt is analyzed by comparing in-situ melt rates calculated via the three-equation parameterization, which was developed for application under ice shelves, with the commonly used bulk parameterization of iceberg basal melt. Our results suggest an updated velocity-independent version of the basal melt parameterization for tabular icebergs for use in calculating the basal melt rate of icebergs that are large (relative to the deformation radius), to account for the changes in ocean properties caused by the physical presence of a large iceberg in the ocean.